The job security for female public relations workers in the hotel field: A field study in the city of Sulaymaniyah - Qader, Zhiya; Mohammed, Lana (Humanities Journal of University of Zakho, 2022)
The aim of the current study is to know the extent to which female workers in public relations, especially in hotel institutions, feel job security towards their profession, and what are the obstacles that cause them to lose the elements of job security within hotel institutions, and for the purpose of reaching scientific results, the descriptive survey method was used in this study. The study sample is represented by a comprehensive inventory of all female workers in the departments (management, marketing, media, sales, reception) for the fifth, fourth, third class hotels in the center of the city of Sulaymaniyah, as the number of respondents reached (89), through the distribution of a questionnaire form to them specially built for this The subject, as for the most prominent findings of the study from the conclusion, that the human dimension is the main influence on the extent of women workers in public relations in the hotel field sense of job security, especially the dimensions related to work relations within the elements of job security within the hotel institution, which is an important motive for the advancement of work, and lack of understanding The senior management of the hotel establishment for the problems of female workers in qualitative public relations was one of the most important obstacles that prevent female workers from feeling job security. Jah their jobs.